The right response: how organisations should react to security incidents. Issue 12 (December 2017) - Mansfield-Devine, Steve
Abstract : The maxim that 'it's not a case of if your organisation gets breached but when' is getting a little tired. And its overuse could be a problem. As Stuart Reed, a senior director at NTT Security, explains in this interview, it leads to a fatalistic and partial outlook on information security at a time when organisations need a far more rounded view – albeit one in which incident response assumes an ever-greater significance. The maxim that 'it's not a case of if your organisation gets breached but when' is getting a little tired. And its overuse could be a problem. As Stuart Reed of NTT Security explains in this interview, this attitude leads to a fatalistic and partial outlook on information security at a time when organisations need a far more rounded view – albeit one in which incident response assumes an ever-greater significance. And he explains how to create a robust incident response plan that starts with understanding the risks you face.